Proper Use of Mooring Lines on Ships to Ensure a Smooth Berthing Process on The MT. Giat Armada 04 - Bima Surya Pulung Sakti; Elise Dwi Lestari; Elly Kusumawati; Upik Widyaningsih (Journal of Engineering Science and Technology Management, 2026)
This study aims to analyze the influence of the physical condition of mooring lines and supporting mooring components on the smooth berthing process of MT. GIAT ARMADA BERSAMA 04. The berthing process is a critical operational phase requiring a highly reliable mooring system to ensure the safety of the vessel, cargo, crew, and port facilities. Employing a qualitative descriptive method, data were collected through field observations across 12 berthing operations, structured interviews with deck officers, and document analysis. The findings revealed that the physical deterioration of the spring lines—specifically characterized by a visible diameter reduction, bird-caging, and surface abrasion exceeding the 10% broken strand threshold—contributed to severe operational difficulties. Furthermore, corroded deck fittings increased mechanical friction, leading to ropes jamming in the mooring chocks and significant delays in tension adjustment. Evaluated against the retirement criteria and inspection parameters defined by the OCIMF Mooring Equipment Guidelines (MEG4) and IMO safety mandates, the vessel’s mooring components operated below acceptable minimum breaking load (MBL) safety margins. Immediate replacement of degraded lines and the implementation of a strict Line Management Plan (LMP) are imperative to restore operational precision, mitigate occupational hazards, and enhance overall port efficiency.